Effect of initial mixing process and calcination temperature on magnetic properties of La–Ca–Co doped strontium ferrite - Muhammad Haseeb; Yuqing Li; Hongguo Zhang; Muhammad Sabil Farooq; Rongming Liu; Ming Yue (AIP Advances)
This study investigates the significant correlation between preparation techniques, calcination temperatures, and the magnetic properties of La–Ca–Co-doped strontium ferrite. By comparing typical dry mixing and wet mixing processes and investigating the effects of different calcination temperatures, this work reveals detailed insights into how to optimize the magnetic performance of these materials. Results show that dry mixing at 1260 °C produces the largest magnetic energy product (35.4 kJ/m3) when sintered at 1225 °C, with a maximum remanence of 437 mT and coercivity of 384 kA/m. Conversely, wet mixing at 1230 °C produces the optimal magnetic performance as a coercivity of 415 kA/m, remanence of 435 mT and (BH)max of 33.4 kJ m−3 at a sintering temperature of 1215 °C. Wet mixing is better for low-temperature calcination due to reduced particle size, greater specific surface area, and lower energy needs. The dry mixing technique at 1260 °C and the wet mixing process at 1230 °C yield good magnetic characteristics for La–Ca–Co doped strontium ferrite. The importance of calcination temperatures and preparation methods on the magnetic properties of doped ferrite is highlighted in this research.